ANTIMICROBIAL ACTIVITY OF PINEAPPLE (ANANAS COMOSUS L. MERR) EXTRACT AGAINST MULTIDRUG-RESISTANT OF PSEUDOMONAS AERUGINOSA: AN IN VITRO STUDY - Zharfan, Rahmat Sayyid; Purwono, Priyo Budi; Mustika, Arifa (Institute of Topical Disease Universitas Airlangga, 2017)
Pseudomonas aeruginosa is the main cause of nosocomial infection which is responsible for 10% of hospital-acquired infection. Pseudomonas aeruginosa tends to mutate and displays potential for development of antibiotic resistance. Approximately, 10% of global bacterial isolates are found as Multidrug-resistant Pseudomonas aeruginosa. Pseudomonas aeruginosa have a quite tremendous severity index, especially on pneumonia and urinary tract infections, even sepsis, which 50% mortality rate. Pineapple (Ananas comosus L. Merr) has antimicrobial properties. The active antimicrobial compounds in Ananas comosus L. Merr include saponin and bromelain. This research aims to find the potency of antimicrobial effect of pineapple (Ananas comosus L. Merr) extract towards Multidrug-resistant Pseudomonas aeruginosa. Multidrug-resistant Pseudomonas aeruginosa specimen is obtained from patient's pus in orthopaedic department, Dr Soetomo Public Hospital, Surabaya. Multidrug-resistant Pseudomonas aeruginosa specimen is resistant to all antibiotic agents except cefoperazone-sulbactam. This research is conducted by measuring the Minimum Inhibitory Concentration (MIC) through dilution test with Mueller-Hinton broth medium. Pineapple extract (Ananas comosus L. Merr.) is dissolved in aquadest, then poured into test tube at varying concentrations (6 g/ml; 3 g/ml; 1.5 g/ml; 0.75 g/ml, 0.375 g/ml; and 0.1875 g/ml). After 24 hours' incubation, samples are plated onto nutrient agar plate, to determine the Minimum Bactericidal Concentration (MBC). The extract of pineapple (Ananas comosus L. Merr) has antimicrobial activities against Multidrug-resistant Pseudomonas aeruginosa. Minimum Inhibitory Concentration (MIC) could not be determined, because turbidity changes were not seen. The Minimum Bactericidal Concentration (MBC) of pineapple extract (Ananas comosus L. Merr) to Multidrug-resistant Pseudomonas aeruginosa is 0.75 g/ml. Further study of in vivo is needed.